2022
DOI: 10.3389/fnins.2022.1069484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation on brain cytokine levels in rats

Abstract: Transcranial direct current stimulation (tDCS) has shown therapeutic potential to mitigate symptoms of various neurological disorders. Studies from our group and others used rodent models to demonstrate that tDCS modulates synaptic plasticity. We previously showed that 30 min of 0.25 mA tDCS administered to rats induced significant enhancement in the synaptic plasticity of hippocampal neurons. It has also been shown that tDCS induces expression of proteins known to mediate synaptic plasticity. This increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Consistently applying multiple tDCS sessions can potentially modulate these biological cascades, determining a significant reduction in angiopoietin-2 and IP-10, for example. The role of tDCS in neuroinflammation has been previously addressed in animal models [ 59 , 60 ] and other neurological conditions, such as bipolar disorders [ 35 ], leading to the hypothesis that tDCS can influence cytokine release in the brain and reduce neural inflammation. Here, importantly, we showed that some biomarkers, i.e., TNFα and IP-10, directly correlate with behavioural changes after the tDCS, as measured by the CRS-R scale.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently applying multiple tDCS sessions can potentially modulate these biological cascades, determining a significant reduction in angiopoietin-2 and IP-10, for example. The role of tDCS in neuroinflammation has been previously addressed in animal models [ 59 , 60 ] and other neurological conditions, such as bipolar disorders [ 35 ], leading to the hypothesis that tDCS can influence cytokine release in the brain and reduce neural inflammation. Here, importantly, we showed that some biomarkers, i.e., TNFα and IP-10, directly correlate with behavioural changes after the tDCS, as measured by the CRS-R scale.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study provided evidence in favor of the excitation/inhibition imbalance hypothesis in ASD and related neurodevelopmental disorders while revealing that its nature is region-specific with distinct pre- and postsynaptic mechanisms. In the hippocampus, disproportionate expression of gamma-aminobutyric acid (GABA)-A receptor dominates, whereas excessive GABA/glutamate ratios are the hallmark of changes in the prefrontal cortex and striatum ( 19 ).…”
Section: Role Of Rtms In Asd Processingmentioning
confidence: 99%